High Hematocrit Resulting from Administration of Erythropoiesis-stimulating Agents Is Not Fully Predictive of Mortality or Toxicities in Preclinical Species. (April 2014) - Andrews, Dina A.; Pyrah, Ian T. G.; Boren, Babette M.; Tannehill-Gregg, Sarah H.; Lightfoot-Dunn, Ruth M.
We conducted a retrospective analysis of publicly available preclinical toxicology studies with erythropoiesis-stimulating agents (ESAs) to examine common adverse events in rats, Beagle dogs, and cynomolgus monkeys. Mortality and/or thrombotic events were reported sporadically in a subset of studies and attributed to the high hematocrit (HCT) achieved in the animals. However, similarly high HCT was achieved in both high-dose and low-dose groups, but there were no reported adverse events in the low-dose group suggesting HCT was not the sole contributing factor leading to toxicity. Our analysis indicated that increased dose, dose frequency, and dosing duration in addition to high HCT contributed to mortality and thrombosis. To further evaluate this relationship, the incidence of toxicities was compared in rats administered an experimental hyperglycosylated analog of recombinant human erythropoietin (AMG 114) at varying dosing schedules in 1-month toxicity studies. The incidence of mortality and thrombotic events increased in higher dose groups and when dosed more frequently, despite a similarly high HCT in all animals. The results from the investigative study and retrospective analysis demonstrate that ESA-related toxicities in preclinical species are associated with dose level, dose frequency, and dosing duration, and not solely dependent upon a high HCT.